Automated detection of endotracheal tubes in paediatric chest radiographs. Issue 1 (January 2015) - Kao, E-Fong; Jaw, Twei-Shiun; Li, Chun-Wei; Chou, Ming-Chung; Liu, Gin-Chung
Highlights We developed a computerised method for the automated detection of the endotracheal tubes and tip positions in paediatric chest radiographs. In the proposed method, a seed point was determined first from a line crossing the cervical region and was used as the initial point to trace a line path. Two features determined from the path were combined to detect the existence of the endotracheal tube, and multiple thresholds were used to determine the tip location. The proposed method was evaluated using 528 images with endotracheal tubes and 816 images without endotracheal tubes. The discriminant performance in this study, evaluated as Az (area under the ROC curve), for detecting the existence of endotracheal tubes was 0.943 ± 0.009, and the detection error of the tip location was 1.89 ± 2.01 mm.